The use of objective adherence measures targeting four placebo microbicide delivery forms in the Quatro Clinical Crossover Study - Terry A. Jacot; Oluwatosin E. Adedipe; Susan Godbout; Abby G. Peele; Jill L. Schwartz; Susan Ju; Tina D. Cunningham; Elizabeth Montgomery; Ariane van derStraten; Mags Beksinska; Jenni Smit; Nyaradzo Mgodi; et al. (Clinical and Translational Discovery, 2021)
Abstract Background Adherence to topical microbicides for HIV prevention has been a challenge for women using them and those developing novel products. The Quatro Clinical Crossover Study investigated user preference and acceptability of four different placebo‐based vaginal delivery forms among young African women. The objective of this sub‐study was to test the ability of objective adherence measures in assessing placebo product usage. Methods A total of two hundred women from Zimbabwe and South Africa used placebo vaginal gel, insert, and film once per week, with or without sex, for 1 month and an intravaginal ring continuously for one month (Months 1–4). Women then chose their preferred product and used it with sex each week during Month 5. Women self‐collected vaginal swabs after using the gel, insert and film. Collected vaginal swabs and used intravaginal rings were analysed for placebo‐based adherence measures using spectroscopy and excipient‐based analyses to determine product use. Vaginal insertion and semen exposure was determined using previously developed and published adherence biomarkers. Intravaginal rings were extracted for residual excipient (glycerin) and penetrated bioanalytes. Results Both methodologies showed that women used gel the most during Months 1–4 (75% by excipient methods, 85% by spectroscopy). The methodologies also determined that nearly all swabs from both sites were vaginally inserted, and 51–86% had detectable placebo product. Semen was detected in more swabs collected during Month 5 from women in Zimbabwe than the swabs from women in South Africa, and most of those swabs had placebo product present as well. The majority of women used the ring for the required four weeks. Sixty‐eight per cent of women who used the ring for the required 4 weeks increased to 78% during Month 5. Conclusion This sub‐study demonstrated how these objective placebo‐based measures of adherence determined product use of various microbicide delivery forms.